Fluorescent Labeling and 2-Photon Imaging of Mouse Tooth Pulp Nociceptors. (April 2018) - Kadala, A.; Sotelo-Hitschfeld, P.; Ahmad, Z.; Tripal, P.; Schmid, B.; Mueller, A.; Bernal, L.; Winter, Z.; Brauchi, S.; Lohbauer, U.; Messlinger, K.; Lennerz, J.K.; et al.
Retrograde fluorescent labeling of dental primary afferent neurons (DPANs) has been described in rats through crystalline fluorescent DiI, while in the mouse, this technique was achieved with only Fluoro-Gold, a neurotoxic fluorescent dye with membrane penetration characteristics superior to the carbocyanine dyes. We reevaluated this technique in the rat with the aim to transfer it to the mouse because comprehensive physiologic studies require access to the mouse as a model organism. Using conventional immunohistochemistry, we assessed in rats and mice the speed of axonal dye transport from the application site to the trigeminal ganglion, the numbers of stained DPANs, and the fluorescence intensity via 1) conventional crystalline DiI and 2) a novel DiI formulation with improved penetration properties and staining efficiency. A 3-dimensional reconstruction of an entire trigeminal ganglion with 2-photon laser scanning fluorescence microscopy permitted visualization of DPANs in all 3 divisions of the trigeminal nerve. We quantified DPANs in mice expressing the farnesylated enhanced green fluorescent protein (EGFPf) from the transient receptor potential cation channel subfamily M member 8 (TRPM8 EGFPf/+ ) locus in the 3 branches. We also evaluated the viability of the labeled DPANs in dissociated trigeminal ganglion cultures using calcium microfluorometry, and we assessed the sensitivity to capsaicin, an agonist of the TRPV1 receptor. Reproducible DiI labeling of DPANs in the mouse is an important tool 1) to investigate the molecular and functional specialization of DPANs within the trigeminal nociceptive system and 2) to recognize exclusive molecular characteristics that differentiate nociception in the trigeminal system from that in the somatic system. A versatile tool to enhance our understanding of the molecular composition and characteristics of DPANs will be essential for the development of mechanism-based therapeutic approaches for dentine hypersensitivity and inflammatory tooth pain.